THE MAIN CHARACTERISTIC OF A GENERAL CURRENT IN THE SOUTH-EASTERN CONTINENTAL SHELF REGION OF VIETNAM - Xuan, Nguyen Ba; Tuan, Nguyen Xuan (Vietnam Journal of Marine Science and Technology, 2006)
THE MAIN CHARACTERISTIC OF A GENERAL CURRENT IN THE SOUTH-EASTERN CONTINENTAL SHELF REGION OF VIETNAM